Description of Temnothorax estel sp. nov. (Hymenoptera: Formicidae), with a review of the Iberian species of the sordidulus species-complex - Arcos González, Javier (Zootaxa, 2021)
A characteristically bicolored ant belonging to the Temnothorax sordidulus species-complex is described from mountainous habitats in Iberia and named T. estel sp. nov. Three additional and closely-related taxa are newly recognized as members of the complex, including the Iberian endemics T. ibericus (Menozzi, 1922) and T. platycephalus (Espadaler, 1997) and the Pyrenean T. conatensis Galkowski & Lebas, 2016. The taxonomy of all four species is reviewed and discussed within the Palearctic context. Images and an identification key are provided.